2017
DOI: 10.1037/aca0000131
|View full text |Cite
|
Sign up to set email alerts
|

Exploring everyday encounters with street art using a multimethod design.

Abstract: In a combination of an outdoor and a laboratory study, we tested how people encountered sculptures and graffiti in an everyday setting. To accomplish an ecologically valid design, we let 12 participants engage in a free exploration walk at the Danube Canal in Vienna, Austria, equipped with a mobile eye tracker. To further investigate our field measures, we conducted a follow-up laboratory session, in which the participants commented on first-person videos from their own walks. After watching the video, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 49 publications
2
36
0
1
Order By: Relevance
“…-No correlations between subjective evaluations and eye movements (Heidenreich & Turano, 2010;Massaro et al, 2012). -Liking and interest predict positively total fixation time for graffiti art and sculptures (Mitschke, Goller, & Leder, 2017). -Increase in fixation durations is greater when paintings are liked more (Plumhoff & Schirillo, 2009).…”
Section: Subjective Evaluations Of Artworkmentioning
confidence: 98%
See 1 more Smart Citation
“…-No correlations between subjective evaluations and eye movements (Heidenreich & Turano, 2010;Massaro et al, 2012). -Liking and interest predict positively total fixation time for graffiti art and sculptures (Mitschke, Goller, & Leder, 2017). -Increase in fixation durations is greater when paintings are liked more (Plumhoff & Schirillo, 2009).…”
Section: Subjective Evaluations Of Artworkmentioning
confidence: 98%
“…Despite the fact that the latter is a theoretically sound assumption (Pelowski et al, 2016), analyses using subjective ratings as correlates or predictors of various eye-movement parameters are employed rather rarely. However, results of some studies suggest that total dwell time increases with increasing subjective ratings of liking or interest (Brieber, Nadal, Leder, & Rosenberg, 2014;Mitschke, Goller, & Leder, 2017;Plumhoff & Schirillo, 2009), complexity (Chassy, Lindell, Jones, & Paramei, 2015), or ambiguity (Brieber et al, 2014; see Table 1 for more details). Consequently, we expected that subject-related cognitive challenge would also positively predict visual exploration not only when it came to dwell time but also other parameters, such as, for example, duration and number of fixations.…”
Section: Subjective Evaluations Of Artworkmentioning
confidence: 99%
“…Installation art also adds the unique aspect of the mobile viewer and the inclusive environment, with an individual who may potentially engage with any aspect of the spaces as part of their encounter. Here too, although some emerging studies have shown the ability to generally track patterns of movement or body responses in the gallery (i.e., heartrate and standing patterns when looking at more or less interesting art, Tröndle et al, 2014a ) this has generally not been considered in conjunction with complex emotional/cognitive experience (see Mitschke et al, 2017 for discussion of the key intrigue and need for such studies in empirical aesthetics). Although not specifically necessary, researchers would also benefit from access to curators and artists, especially when considering their making decisions and specific goals for evoking certain response, which may also be useful in forming hypotheses and assessing the efficacy of the works.…”
Section: Review—installation Art: Research Questions Issues and Appmentioning
confidence: 99%
“…However, the technique, which can record looking patterns of a mobile, walking viewer, is especially useful for an installation environment where any part of the environment might be a point of attention. This study followed our recent work in real–world art interaction contexts, specifically Mitschke et al (2017) which employed the same technology as viewers walked along a riverside path with a number of installed sculptures, graffiti art, in conjunction with the ambient visual environment. This study showed good ability to record general patterns of looking and attention on the different objects.…”
Section: Review—installation Art: Research Questions Issues and Appmentioning
confidence: 99%
“…2011;Yeung et al 2016;De Pascalis et al 2017), children on the autism spectrum (Thorup et al 2016;Nyström, et al 2017) and people otherwise unable to communicate (Galdi et al 2016;Hong et al 2017;Lee 2017). It has been used to study differences in sensory processing between experts versus novices in a given area, such as art production and evaluation (Zhiwei and Qiang 2004;Rosenberg and Klein 2015;Mitschke et al 2017;Bauer and Schwan 2018), athletic activities (Krzepota et al 2016;Decroix et al 2017;Vickers et al 2017) and other physically related skills (van Leeuwen et al 2017), teaching (McIntyre et al 2017, and medical diagnoses (Södervik et al 2017). It has also been used to investigate ways in which pre-existing dispositional attitudes and attitudinal states influence socially relevant sensory processing (Kawakami et al 2014;Flechsenhar and Gamer 2017;Frazier et al 2017).…”
mentioning
confidence: 99%